Effect Of Isolated And Combined Training Of Aerobic And Yoga On Mean Arterial Pressure Among Football Players (International Journal of Food and Nutritional Sciences, 2022)
The purpose of the study was to find out the effect of isolated and combined training of aerobic and yoga on mean arterial pressure among football players. To achieve this purpose of the study, sixty male football were selected as subjects who were from the Mar Athanasius College of Engineering, Kothamangalam